Evaluation of Protection of Critical Infrastructure in Nigeria. A Case Study of Protection of Power Facilities in Abuja - Saladin Quadri Adigun (European Scientific Journal, ESJ, 2018)
This research work investigated the protection of critical infrastructure in Nigeria with special attention to electric power infrastructure within Federal Capital Territory (FCT), Abuja. The study was guided by six research questions and the instrument employed for the research was titled ‘Evaluation of the Effectiveness of Protection of Critical Infrastructure’ (EEPCI). The study was carried out among the consumers of electricity in three of the six Area Councils, the security personnel employed to guard as well as the workers of the power facilities called Abuja Electricity Distribution Company (AEDC) and Transmission Company of Nigeria (TCN) in the capital territory. The entire population of the study was 3,750 and this cut across the strata of the stakeholders in power industry. The data gathered were analyzed by the use of frequency, percentages and statistical mean distribution technique. Findings from the study showed that the existing protection techniques are weak, unassertive and the power companies are slow to mitigating effects of attacks on their facilities. Based on the findings, the researcher recommended that policies and equipment protection strategies be utilized by the power companies and the government. The study laid emphasis on establishment of community anti-crime group and provision of free toll hotline for emergency purposes. Furthermore, the penalty for damages to power facilities was recommended to be stiffer and the security should be empowered to excel in their profession.